A new genus and three new species of Empoascini (Hemiptera: Cicadellidae: Typhlocybinae) from China - Ding, Yan; Yan, Bin; Yu, Xiao-Fei; Yang, Mao-Fa (Zootaxa, 2024)
One new genus and three new species of Empoascini from China are described and illustrated: Ventriappendix Ding, Yu & Yang gen. nov. with a new species V. divaricata Ding, Yu & Yang, sp. nov.; Dayus motuoensis Ding, Yu & Yang sp. nov.; and Alebroides hei Ding, Yu & Yang sp. nov. A revised key to males of Chinese species and a checklist to the genus of Dayus are also provided.